Co-citation scientific maps: A case study of medical sciences in Iran - Hariri, Nadjla; Shekofteh, Maryam; Salahi Yekta, Ali (Archives of Advances in Biosciences, 2012)
Visualization of scientific maps enhances the awareness and general recognition of the scientific domains and their structures. It facilitates the study of the existing situation and planning of the future researches as well. The present study sought to discover and generate the scientific map of medicine in Iran between 2003 and 2007. It also aimed to determine the most effective medical subject categories in the map generated. The study follows a scientometrics trend in which all published articles of Iran indexed in the Science Citation Index Expanded (SCIE) between 2003 and 2007 were retrieved. Then, these articles were limited to medical subject categories through the result analysis section of SCIE and 10247 articles were retrieved in medical subject categories as research population. NWB (Network Workbench Tool) software and ISI medical subject category co-citation were used for analyzing the articles in medicine and generating scientific maps. The scientific medical map showed that there were 61 nodes and 164 links with a weight ranging from 101 to 591. 31 nodes depicted one medical subject category, while the other nodes covered non-medical, or a combination of medical and non-medical subject categories. Medical subject categories with the highest impact included general and internal medicine, pharmacology and pharmacy, biochemistry and molecular biology, neurosciences, and research and experimental medicine. The strongest links were visible in general and internal medicine, with public, occupational, and environmental health; general and internal medicine with pharmacology and pharmacy; and pharmacology and pharmacy with neurosciences. The quantitative growth in medical articles alongside their quality is effective in scientific maps. It is necessary to encourage the categories with more effective and support the subject categories with the least impact to publish more articles and get more citation.